Comparison between Examination with Naked Eye, Curretage and Dermoscopy in Determining Tumor Extension before Mohs Micrographic Surgery - Ali Asilian; Iman Momeni; Mohammad Ali Nilforoushzadeh (مجله دانشکده پزشکی اصفهان, 2015)
Background: Mohs micrographic surgery (MMS) is a technique for the treatment of cutaneous malignancies. Subtle determination of tumor margin would end to fewer stages of surgery. Our aim was to compare three ways for determining tumor extension before initiation of MMS, examination with the naked eye, dermoscopy and curettage. Methods: Sixty patients with basal cell carcinoma (BCC) in head and neck area were randomized in three groups (curettage, dermoscopy and examination with the naked eye). Each group encompassed twenty patients. The total number of resection stages in MMS was recorded for each patient. Demographic data of the patients and the total number of resection stages in MMS were statistically analyzed. Findings: Based on the results of analysis of variance (ANOVA) test, there was no significant difference for total number of stages between three groups (P = 0.1). The Pearson correlation coefficient showed a direct relation between the age and resection stages (r = 0.19; P = 0.04). The chi‑square test showed no differences between three groups regarding age, residence and radiotherapy history. Conclusion: This study showed that none of the studied methods is better for determining tumor extension before initiation of MMS. Key Words: Curettage, Basal cell carcinoma, Dermoscopy, Mohs micrographic surgery